2020
DOI: 10.1097/sla.0000000000004265
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning for Severe Acute Respiratory Distress Syndrome in COVID-19 Patients by a Dedicated Team

Abstract: Objective: The aim of this study was to define whether rapidly reallocating health care workers not experienced with PP for performing PP in ICU is feasible and safe. Summary Background Data: In the setting of severe acute respiratory distress syndrome (ARDS), the use of prone and supine positioning procedures (PP) has been associated with improved oxygenation resulting in decreased mortality. Nevertheless, applying PP is time consuming for ICU staffs that are at risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
(6 reference statements)
0
27
0
2
Order By: Relevance
“…Similarly, some groups addressed the incidence of pronation-related complications in critically ill COVID-19 patients [ 19 , 20 ]. In this setting, Short et al [ 21 ] reported a clinical benefit in having a specific “pronation team” dedicated to patients’ pronation during the pandemic wave [ 22 ], even though they focused mainly over clinical patients evolution, rather than over the rate of complications related to this delicate procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some groups addressed the incidence of pronation-related complications in critically ill COVID-19 patients [ 19 , 20 ]. In this setting, Short et al [ 21 ] reported a clinical benefit in having a specific “pronation team” dedicated to patients’ pronation during the pandemic wave [ 22 ], even though they focused mainly over clinical patients evolution, rather than over the rate of complications related to this delicate procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative solutions have been found worldwide to cope with limited resources and to include the prone positioning in the management of patients requiring mechanical ventilation, even at the surge of the outbreak, resulting in the emergence of prone teams ( Doussot et al, 2020 ; Kimmoun et al, 2020 ; Settembre et al, 2020 ).…”
Section: On the Interest Of Prone Positioning In Covid-19 Pneumonia mentioning
confidence: 99%
“…Comme les études de modélisation ont évoqué une telle possibilité pour les hôpitaux canadiens si les mesures demandées par la santé publique ne sont pas respectées 35,36 , les hôpitaux devraient par conséquent préparer ou adopter des lignes de conduite concernant le décubitus ventral, promouvoir un transfert rapide des connaissances et la formation du personnel clinique. À titre d'exemple, Doussot et ses collègues ont décrit la création d'une équipe spécialisée pour le décubitus ventral dans un hôpital régional en France 37 . Chirurgiens, personnel infirmier, physiothérapeutes et autres professionnels de la santé ont accepté de recevoir la formation, qui incluait une liste de vérification, une simulation et une formation sur l'utilisation appropriée de l'EPI 37 .…”
Section: Quels Sont Les Enjeux Logistiques De L'utilisation Du Décubitus Ventral Durant La Pandémie De Covid-19?unclassified
“…À titre d'exemple, Doussot et ses collègues ont décrit la création d'une équipe spécialisée pour le décubitus ventral dans un hôpital régional en France 37 . Chirurgiens, personnel infirmier, physiothérapeutes et autres professionnels de la santé ont accepté de recevoir la formation, qui incluait une liste de vérification, une simulation et une formation sur l'utilisation appropriée de l'EPI 37 .…”
Section: Quels Sont Les Enjeux Logistiques De L'utilisation Du Décubitus Ventral Durant La Pandémie De Covid-19?unclassified